Teachers and students perception towards bullying in Batu Pahat district secondary school - Yahaya, Azizi; Ramli, Jamaluddin; Hashim, Shahrin; Ibrahim, Mohd. Ali; Raja Abd. Rahman, Raja Roslan (EurojournalPublication, 2009)
This study also attempts to identify the perception of the students and teachers about bullying in secondary schools. Beside that this study also attempts to identify students perception about safety issues at secondary schools. 80 teachers and 480 students from eight secondary schools in Batu Pahat were randomly selected in this study. All information was gathered through Peer Relations Questionnaire - PRQ and The Nature and Prevalence of Bullying in Schools Questionnaire. The alpha cronbach for these two instruments were 0.7010 and 0.8097. Results have shown that there is a different perception about the prevalence of bullying among secondary school students and teachers. Students reported that the overall rate of the bullying prevalence were at moderate level where as teachers reported the bullying prevalence overall rate were at low level. There is no significant on the prevalence of bullying between male and female students but there is a significant difference on the prevalence between verbal bullying and physical bullying. Verbal bullying was seen more frequent compare to physical bullying.